MEDI1873, a potent, stabilized hexameric agonist of human GITR with regulatory T-cell targeting potential. (4th March 2017) - Tigue, Natalie J.; Bamber, Lisa; Andrews, John; Ireland, Samantha; Hair, James; Carter, Edward; Sridharan, Sudharsan; Jovanović, Jelena; Rees, D. Gareth; Springall, Jeremy S.; Solier, Emilie; Li, Yi-Ming; et al.
ABSTRACT: Glucocorticoid-induced tumor necrosis factor receptor-related protein (GITR) is part of a system of signals involved in controlling T-cell activation. Targeting and agonizing GITR in mice promotes antitumor immunity by enhancing the function of effector T cells and inhibiting regulatory T cells. Here, we describe MEDI1873, a novel hexameric human GITR agonist comprising an IgG1 Fc domain, a coronin 1A trimerization domain and the human GITRL extracellular domain (ECD). MEDI1873 was optimized through systematic testing of different trimerization domains, aglycosylation of the GITRL ECD and comparison of different Fc isotypes. MEDI1873 exhibits oligomeric heterogeneity and superiority to an anti-GITR antibody with respect to evoking robust GITR agonism, T-cell activation and clustering of Fc gamma receptors. Further, it recapitulates, in vitro, several aspects of GITR targeting described in mice, including modulation of regulatory T-cell suppression and the ability to increase the CD8 + :CD4 + T-cell ratio via antibody-dependent T-cell cytotoxicity. To support translation into a therapeutic setting, we demonstrate that MEDI1873 is a potent T-cell agonist in vivo in non-human primates, inducing marked enhancement of humoral and T-cell proliferative responses against protein antigen, and demonstrate the presence of GITR- and FoxP3-expressing infiltrating lymphocytes in a range of human tumors. Overall our data provide compelling evidence that MEDI1873 is a novel, potent GITR agonist with the ability to modulate T-cell responses, and suggest that previously described GITR biology in mice may translate to the human setting, reinforcing the potential of targeting the GITR pathway as a therapeutic approach to cancer.